Electronics in South Asia - Narain, Ashish (World Bank, Washington, DC, 2016)
The electronics sector has played an important role in the development trajectories of several newly industrialized economies. South Asia’s lack of competitiveness reflects inadequate provision of public goods (e.g. industrial zones next to world class ports and urban centers) rather than high labor costs or low productivity. The analysis focuses primarily on India and Sri Lanka – the two countries which already have a critical mass of companies in the electronics sector – and touches on Bangladesh. This case study identifies both reasons for success and limits on the growth of electronics in South Asia, and recommends policies to enhance its growth.